2015
DOI: 10.1007/s11104-015-2590-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fungal endophytes associated with rice roots from irrigated and upland ecosystems in Kenya

Abstract: Background and aim Fungal endophytes are commonly associated with plants, and are considered an important component of crop production. They can influence plant growth and tolerance to biotic and abiotic stresses. The aim of this study was to analyse and identify endophytic fungi associated with rice roots in irrigated and upland ecosystems in Kenya, as an inventory for a future search for biological control and growth promoting agents. Methods Fungi were isolated from the roots and selected based on culture c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Our results showed that the fungal community composition in the studied land use systems was similar to an ITS-based analysis [9]. Eurotiales and Hypocreales are described as endophytes [50,51], further supporting the assumption that the reduction of plant diversity also reduces endophyte occurrence. In addition to fungi, we analysed protists within the eukaryotes but the obtained trophic groups did not show significant differences in abundance in contrast to an 18S rRNA gene-based study [10].…”
Section: Discussionsupporting
confidence: 77%
“…Our results showed that the fungal community composition in the studied land use systems was similar to an ITS-based analysis [9]. Eurotiales and Hypocreales are described as endophytes [50,51], further supporting the assumption that the reduction of plant diversity also reduces endophyte occurrence. In addition to fungi, we analysed protists within the eukaryotes but the obtained trophic groups did not show significant differences in abundance in contrast to an 18S rRNA gene-based study [10].…”
Section: Discussionsupporting
confidence: 77%
“…Like previous studies [54,74], carrot taproots in our trial were colonized by an abundant (Fig 2) and diverse assortment of endophytic microbes (Table 4) We recovered 28 distinct taxa (Table 4), though we suspect that the total diversity of endophytes present in carrot taproots could be even higher. For example, other studies have isolated between 92 to 1000 bacterial and 75 to 350 fungal species in the roots of other plant species [75][76][77][78][79][80][81][82]. Consequently, we expect that by using alternative techniques such as next generation sequencing, additional endophytic taxa will be identified in carrot taproots.…”
Section: Plos Onementioning
confidence: 99%
“…Endophytes, microbiome and plants under other conditions Pili et al (2016) characterized the endophytic fungi assemblage associated with rice roots in irrigated and upland ecosystems in Kenya. The study was focused on Fusarium oxysporum (FOSC) and Gibberella fujikuroi (GFSC) species complexes, but more fungal species were found in the irrigated ecosystems than in the upland ecosystems.…”
Section: Endophytes Microbiome and Extreme Conditionsmentioning
confidence: 99%